Difficult texts: Matthew 10.37 - Martin, David 1929-2019 (2015)
The article discusses the application of radical dominical sayings outside the specific contexts that elicited them, and specifically looks at those sayings seemingly subverting the Law relating to the family when it is clear Jesus elsewhere accepted it and, moreover, confined his message to the Jews. It also notes the centrality of radical sayings about the problems of power and wealth and the marginality of those issues of sexuality and family that touch us most nearly.
Keywords: Bibel